The Experimental Study of the Effect of Adding High-Molecular Polymers on Heat Transfer Characteristics of Nanofluids - Guzei Dmitriy; Pryazhnikov Maxim; Minakov Andrey; Zhigarev Vladimir (MATEC Web of Conferences, 2016)
The experimental study of influence of adding high-molecular weight polymers on heat transfer characteristics of water-based nanofluids with Al 2 O 3 nanoparticles. Volumetric concentration of particles was very low, 10-3 %. The volumetric particle concentration was equal to 2%. We investigated the dependence of heat transfer coefficient and pressure drop on the concentration of additives high polymers.